PENDEKATAN STUDI ISLAM: STUDI PERILAKU BERDERMA MASYARAKAT, GAYA HIDUP DAN PERILAKU KONSUMEN MASYARAKAT KELURAHAN BUGIH PAMEKASAN DALAM TINJAUAN HUKUM ISLAM - Miftahul Ulum; Novia Dwi Nastiti; Faizatul Muazzaroh (Jurnal Istiqro, 2021)
This research aims to know how consumen behavior, lifestyle and charitable behavior of Bugih public and the second is how consumen behavior, lifestyle and charitable behavior of Bugih public based of Islamic consumption . This is a fenomelogy research and used qualitative-descriptive method approach. Data was collected by interviews, observations and documentations. The analysis technique by reducing the data, display data, take a conclusion and do verification. The results of this research conclused that consumen behavior, lifelstyle and charitable behavior of Bugih public are, from consumen behavior more fulfill the basic need beetwen others need. They consumen behavior’s influenced by psychologys, cultures, personals and social factor. They prefer quality than price. They have a saving as a sign that they are not excessive. From lifestyle, all of them fulfill the basic need and do balanced, buying a halal things and prefer taking a time at home than go hangout or refreshing. From charitable behavior, they are have a specific time, give it through to the people and no matter about that. Second, based of Islamic consumption, consumen behavior, lifestyle and charitable behavior of Bugih public are suitable with Islamic consumption. From consumen behaviors of Bugih public are fulfill consumption Islamic ethics, they’re buying balance, do and buy halal thing consumptions. From lifestyle, they’re not deviate from Islamic consumption, attention to maslalah and not hangout or refreshing to taking a free time.